Effect of Annealing Temperature on Hydrogen Storage Properties of LaNi3.8Al1.0Mn0.2 Alloy. Issue 4 (April 2016) - Han, Xingbo; Yang, Xiaojun; Wang, Pei; Chen, Wei; Lin, Zifeng; Liu, Guoliang; Chen, Demin; Yang, Ke
Abstract: The LaNi3.8 Al1.0 Mn0.2 hydrogen storage alloy annealed at different temperatures ( T =1173, 1223, 1273, 1323 K) was investigated to examine the effect of annealing temperature on the crystal structure, the activation and the hydrogen absorption/desorption performance. It is found that the non-CaCu5 phases becomes tinier and more dispersive after annealing. All the alloys consist of the same matrix phase with CaCu5 type structure. Although it is more difficult to activate the annealed alloy than the as-cast alloy, the activation becomes easier with the increase of annealing temperature for the annealed alloy. The plateau pressure decreases at first with the increase of annealing temperature, when T ≤1223 K and then increases. Changes in both the lattice strain and the pressure plateau slope factor of S f in the alloys show the same trends with that of the annealing temperature, exhibiting a maximum at T =1223 K. It is also found that the absolute value of the enthalpy increases with the increase of annealing temperature, when T ≤1223 K and then decreases, showing the same change trend as that of the cell volume. Moreover, the pulverization resistance and kinetics of the alloy are improved by annealing. The pulverization resistance is weakened at first with the increase of annealing temperature when T ≤1223 K and then increases, but the kinetics of the alloy is almost not influenced by the annealing temperature.